2014
DOI: 10.1523/jneurosci.0108-14.2014
|View full text |Cite
|
Sign up to set email alerts
|

Plasticity in the Human Speech Motor System Drives Changes in Speech Perception

Abstract: Recent studies of human speech motor learning suggest that learning is accompanied by changes in auditory perception. But what drives the perceptual change? Is it a consequence of changes in the motor system? Or is it a result of sensory inflow during learning? Here, subjects participated in a speech motor-learning task involving adaptation to altered auditory feedback and they were subsequently tested for perceptual change. In two separate experiments, involving two different auditory perceptual continua, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
95
7

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 65 publications
(125 citation statements)
references
References 69 publications
17
95
7
Order By: Relevance
“…Instead, the shift in perception correlated with changes in the motoric behavior, supporting an articulatory basis for the perceptual shift. In line with the results of Lametti et al (2014b), changes in perception were variable and depended on the direction of the articulatory change, rather than universally according with the direction of the shifted auditory feedback.…”
Section: H Discussionsupporting
confidence: 80%
See 4 more Smart Citations
“…Instead, the shift in perception correlated with changes in the motoric behavior, supporting an articulatory basis for the perceptual shift. In line with the results of Lametti et al (2014b), changes in perception were variable and depended on the direction of the articulatory change, rather than universally according with the direction of the shifted auditory feedback.…”
Section: H Discussionsupporting
confidence: 80%
“…Furthermore, the direction of the observed effects suggests that the change in perceptual function corresponds to motoric changes rather than auditory feedback. Previous experiments have found that passive exposure to the recorded speech of a participant compensating in response to AAF fails to change perceptual function, regardless of whether the recorded speech is made by an average compensating speaker (Shiller et al, 2009) or consists of a random selection of stimuli take from several compensating speakers (Lametti et al, 2014b). However, these experiments differed from the present study in that they did not examine how passive listening to such stimuli may affect CFC.…”
Section: Methodscontrasting
confidence: 78%
See 3 more Smart Citations